(untitled) (KYAMC Journal, 2022)
Background: Teaching-learning of Anatomy is become challenging due to change in undergraduate medical curricula and reduction of time allotted for studying Anatomy. Moreover, students are never tried of using memory enhancing techniques like mnemonics that results better retention of recalled anatomical knowledge. But teachers’ experiences regarding different aspects of mnemonics are still sketchy. Objective: To analyze the experiences of the Bangladeshi Anatomy teachers’ in using mnemonics on teaching-learning of Anatomy. Material and Methods: A questionnaire-based survey was conducted to analyze the experiences of 63 Bangladeshi Anatomy teachers regarding different aspects of anatomical mnemonics and their suitability in teaching-learning of Anatomy. Results: Most of the surveyed teachers had experience of using anatomical mnemonics as a student (88%). Most (82%) of them used mnemonics in Regional Anatomy and also got the highest number of choices (90%) as the subdivision of Anatomy where mnemonics are likely to be effective. Most of them relate themselves with memory enhancing techniques in Anatomy. Conclusion: Most of the teachers’ used mnemonics as a student, mostly in Regional Anatomy where the use of mnemonics was likely to be more effective than any other subdivisions of Anatomy. KYAMC Journal. 2022;12(04): 226-230